(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The Labour Reform of 2012 has set important new provisions into our system of determination and adjustment of working conditions at corporate level. This research paper covers the most relevant innovations implemented in the legal framework of each adjustment technique: substantial modification of basic workingconditions laid down by the employer beyond the scope of statutory collective bargaining, temporary deviations from collective agreements, anticipated revision of collective agreements and subscription of collective agreements at company level interms of concurrency with sector-level agreements in force. Finally, we focus on the adjustment measures to be applied at corporate level on minimum working conditions, once the so-called ultra-enforcement of collective agreements expires.